Self-Study and Inquiry into Practice. - Kroll, Linda R. R. (Teacher Quality and School Development., 2012)
There are new pressures and familiar pressures on teacher educators to prepare teachers who will be able to teach successfully in a changing world, and who will be able to change the world. The question of how to prepare well-qualified teachers has become an international question with global responses and consequences. This book describes a stance and pedagogy for helping young teachers to be successful in the most challenging of circumstances. Self-study and Inquiry into Practice describes how inquiry can contribute to effective teaching in urban settings. The use of inquir.